Prevention of DMBA-induced mammary gland tumors in mice by a dual-function inhibitor of JAK3 and EGF receptor tyrosine kinases - Şahin, Kazım; Yabas, Mehmet; Orhan, Cemal; Tuzcu, Mehmet; Sahin, Taha K.; Ozercan, Ibrahim H.; Uckun, Fatih M. (Taylor & Francis Ltd, 2020)
Objectives: We tested the chemopreventive effect of WHI-P131 in side by side evaluation with the standard anti-breast cancer drug paclitaxel in the well-established 7,12-dimethylbenz(a)anthracene (DMBA)-induced breast cancer model. Methods: One hundred BALB/cmice were divided into five groups. (i) Control (ii) DMBA (iii) DMBA+ Paclitaxel (10 mg/kg) (iv) DMBA+WHI-P131 (Janex1, 50 mg/kg of BW, i.p, three times per week) (J) (v) DMBA+P+J. The duration of study was 25 weeks. Results: Our findings demonstrate that WHI-P131 impedes DMBA-induced carcinogenesis, reduces size, weight, and load of tumors (P < 0.001) in DMBA-challenged mice and improves their survival outcome (P < 0.01). The tumors developing despite WHI-P131 chemoprevention displayedattenuated levels of JAK3, STAT3, and NF-kappa B as well as increased I-kappa B expression (P < 0.001). Notably, these tumors exhibited significantly decreased levels of phosphorylated AKT-PI3-Kinase pathway signaling proteins p-mTOR, p-p70S6K1, and p-4E-BP1 (P < 0.001). Our findings are consistent with a model in which DMBA-induced malignant clones with low-level expression of the six signature proteins JAK3/STAT3/NF-kappa B/p-mTOR, p-p70S6K1/p-4E-BP1, albeit not as aggressive as their JAK3/STAT3/NF-kappa B overexpressing counterparts are capable of escaping chemo-preventive effects of WHI-P131. Conclusion: These insights may provide the foundation for new chemo-preventive strategies in which WHI-P131 is applied to prevent the development of aggressive forms of breast cancer.
Keywords: Breast cancer; JAK3 inhibitor; mice; paclitaxel; Whi-P131